Jagged and Delta-like ligands control distinct events during airway progenitor cell differentiation - Stupnikov, Maria R (eLife, 2019)
Notch signaling regulates cell fate selection during development in multiple organs including the lung. Previous studies on the role of Notch in the lung focused mostly on Notch pathway core components or receptor-specific functions. It is unclear, however, how Jagged or Delta-like ligands collectively or individually (Jag1, Jag2, Dll1, Dll4) influence differentiation of airway epithelial progenitors. Using mouse genetic models we show major differences in Jag and Dll in regulation and establishment of cell fate. Jag ligands had a major impact in balancing distinct cell populations in conducting airways, but had no role in the establishment of domains and cellular abundance in the neuroendocrine (NE) microenvironment. Surprisingly, Dll ligands were crucial in restricting cell fate and size of NE bodies and showed an overlapping role with Jag in differentiation of NE-associated secretory (club) cells. These mechanisms may potentially play a role in human conditions that result in aberrant NE differentiation, including NE hyperplasias and cancer.